PELATIHAN PENULISAN IKLAN BERBASIS LITERASI KEBAHASAAN SEBAGAI PENGUATAN BERPIKIR KRITIS DAN KREATIVITAS BAHASA MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Ratnawati; Muhammad Akhir; Sri Lestari Tari; Aulia Rezkyana Agus (STKIP Subang, 2026)
This community service article aims to enhance students’ critical thinking skills and linguistic literacy through creative advertising writing training. The participants were fifth-semester students of the Indonesian Language and Literature Education Program at Universitas Muhammadiyah Makassar. The training employed a participatory approach consisting of lectures, discussions, practice sessions, and evaluations. Data were collected using questionnaires, writing tests, and observations. The results indicate a significant improvement in students’ understanding of linguistic literacy concepts, diction accuracy, sentence effectiveness, and creativity in advertising texts. The training also fostered students’ awareness of ethical and persuasive language use. These findings demonstrate that literacy-based advertising writing training contributes positively to students’ academic and professional competencies.